2019
DOI: 10.3389/fimmu.2019.02021
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1/-33 Signaling Pathways as Therapeutic Targets for Endometriosis

Abstract: Endometriosis is an estrogen-dependent disease with symptoms of dysmenorrhea, chronic pain, and infertility that affects 6–10% of women of reproductive age. Medical or surgical therapy, such as administration of an anti-gonadotropin or ovarian cystectomy, provide effective pain relief. However, neither therapy can be used for patients wishing to become pregnant. Despite the high morbidity, the pathogenesis of endometriosis has not been well-elucidated. Several inflammatory cytokines are reported to participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 57 publications
1
29
1
1
Order By: Relevance
“…It was suggested that cytokine production of NK cells in the peritoneal fluid in women suffering with endometriosis might be changed by dienogest or OCP because of the change of NCRs (Figure 2B). 80 Recently, we have reported the role of IL‐1/IL‐33 signaling in the onset and development of endometriosis 13 . In the absence of IL‐33 or IL‐1R1, endometriotic lesions were reduced.…”
Section: Modification Of Nk Cell Abnormalities In Women With Endometrmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that cytokine production of NK cells in the peritoneal fluid in women suffering with endometriosis might be changed by dienogest or OCP because of the change of NCRs (Figure 2B). 80 Recently, we have reported the role of IL‐1/IL‐33 signaling in the onset and development of endometriosis 13 . In the absence of IL‐33 or IL‐1R1, endometriotic lesions were reduced.…”
Section: Modification Of Nk Cell Abnormalities In Women With Endometrmentioning
confidence: 99%
“…There are many reports suggesting that women with endometriosis have lower success rates of IVF‐ET 11,12 . More importantly, many researchers have reported changes in the functions of immune cells in the peritoneal fluid and cytokine production such as IL‐1, 13,14 IL‐6, 14,15 IL‐8, 14 IL‐33, 13 TNF‐α, 15‐18 IFN‐γ, 16,17 and VEGF 19,20 by immune cells as the cause of infertility. Changes in endometrial lymphocytes and endometrial receptivity have also been reported 21‐23 .…”
Section: Endometriosis and Infertilitymentioning
confidence: 99%
“…Endometriosis lesions are often found attached to the peritoneal wall or in association with the ovaries where they are exposed to PF containing immune cells, cytokines, and growth factors (Bain and Jenkins, 2018;Zondervan et al, 2020). Pro-inflammatory factors increased in the PF of women with endometriosis include interleukins (IL-1, IL-6, IL-8, and IL-33), tumor necrosis factor (TNF), and insulin-like growth factor 1 (Cheong et al, 2002;Forster et al, 2019;Kato et al, 2019). Many cells may contribute to this complex mix of factors with different lines of evidence implicating immune cells, mesothelial cells, as well as endometrial tissue arriving in the peritoneum via retrograde menstruation.…”
Section: Endometriosis As An Inflammatory Disordermentioning
confidence: 99%
“…Members of the IL-1 cytokine family (including IL-33 and IL-1b) and their receptors appear to be promising targets for new therapies with evidence from mouse models that monoclonal antibodies directed against these ligands, as well as inhibitors of their MyD88 downstream signaling pathway, can reduce lesion volume (Kato et al, 2019). IL-33 is released by damaged cells and has been implicated in activation of allergic inflammation-related eosinophils, basophils, mast cells, macrophages, and group 2 innate lymphoid cells (IL-C2s) through its receptor ST2 (Chan et al, 2019).…”
Section: Novel Therapies Targeting Endometriosis As An Inflammatory Disordermentioning
confidence: 99%
“…Inflammatory cytokines are involved in the pathogenesis of endometriosis. The role of interleukin (IL)-1/IL-33 signaling in the development of endometriosis and the effect of the Il-1R-associated kinase (IRAK4, a downstream signal of MyD88) inhibitor have been studied in a mouse model [ 113 ]. IL-1 is involved in the development of endometriosis and MyD88 signaling is essential to the growth of endometriotic lesions.…”
Section: Non-hormonal Treatmentmentioning
confidence: 99%